Strategi Pembelajaran CIRC (Cooperative Integrated Reading and Composition dalam Meningkatkan Pembelajaran Bahasa Arab di MI Darul Ulum Tambak Oso - M. Masrur Huda; Helmi Yuliati Ningsih; Nurul Huda; Nur Azizah (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
This study aims to determine Arabic language learning using CIRC (Cooperative Integrative Reading and Composition) cooperative strategies, analyze the improvement of Arabic language learning using CIRC cooperative strategies and find out the supporting factors and obstacles to CIRC cooperative learning at MI Darul Ulum Tambak Oso. This research uses a qualitative descriptive approach. Data were collected using observation techniques, structured interviews and documentation. Data analysis is carried out through the process of data reduction, data presentation and drawing conclusions continuously, to produce saturated data. The results of the data analysis showed that in theimplementation of the CIRC cooperative learning strategy to improve Arabic learning at MI Darul Ulum Tambak Oso, it was found that: CIRC cooperative learning materials in improving Arabic learning are carried out through the process of student interaction and exchange of ideas with group friends including reading texts that must be understood, writing down the main ideas in the reading text, discussing the main ideas of the reading text, and summing up the material studied in the reading text; Circ Arabic cooperative learning can increase student motivation, including comfort in the learning process, reducing boredom, awakening the courage to express opinions, and encouraging students' concern to encourage each other and teach their friends, so that students can more easily understand the material and more confidently present the results of discussions in front of the class; The successful development of circ Arabic cooperative learning is supported by the competence of teachers in preparing lesson plans and the ability to manage classes. Some factors that need to be anticipated in the cooperative learning of the Arabic CIRC include allocation management, differences in abilities between students, and the arrangement of discussion rooms.